Effect of Lactiplantibacillus plantarum on the conversion of linoleic acid of vegetable oil to conjugated linoleic acid, lipolysis, and sensory properties of cheddar cheese - Khan, Awais (2023)
Conjugated linoleic acid (CLA) is perceived to protect the body from metabolic diseases. This study was conducted to determine the effect of Lactiplantibacillus plantarum (Lp. plantarum) on CLA production and sensory characteristics of cheddar cheese. Lp. plantarum can convert linoleic acid (LA) to CLA. To increase CLA in cheddar cheese and monitor the conversion of LA to CLA by Lp. plantarum, the LA content of cheese milk (3.4% fat) was increased by partially replacing fat with safflower oil (85% LA of oil) at 0, 3, 6, and 9% concentrations (T1, T2, T3, and T4). Furthermore, Lp. plantarum 108 colony-forming units (CFU)/mL (8 log CFU mL−1) was added in all treatments along with traditional cheddar cheese culture (Lactococcus lactis ssp. lactis and L. lactis ssp. cremoris). After 30 days of ripening, Lp. plantarum in T1, T2, T3, and T4 was 6.75, 6.72, 6.65, and 6.55 log CFU g−1. After 60 days of ripening, Lp. plantarum in T1, T2, T3, and T4 was 6.35, 6.27, 6.19, and 6.32 log CFU g−1. After 60 days of ripening, Lp. plantarum in T1, T2, T3, and T4 was 6.41, 6.25, 6.69, and 6.65 log CFU g−1. GC-MS analysis showed that concentrations of CLA in the 90 days’ control, T1, T2, T3, and T4 were 1.18, 2.73, 4.44, 6.24, and 9.57 mg/100 g, respectively. HPLC analysis revealed that treatments containing Lp. plantarum and LA presented higher concentrations of organic acids than the control sample. The addition of safflower oil at all concentrations did not affect cheese composition, free fatty acids (FFA), and the peroxide value (POV) of cheddar cheese. Color flavor and texture scores of experimental cheeses were not different from the control cheese. It was concluded that Lp. plantarum and safflower oil can be used to increase CLA production in cheddar cheese.